Body Mass Index, Diabetes, and Risk of Tuberculosis: A Retrospective Cohort Study - Choi, Hayoung; Yoo, Jung Eun; Han, Kyungdo; Choi, Wonsuk; Rhee, Sang Youl; Lee, Hyun; Shin, Dong Wook (Frontiers in Nutrition, 2021)
Although both diabetes mellitus (DM) and underweight are associated with increased risk of tuberculosis (TB), there are limited data evaluating TB risk while considering two factors simultaneously—body mass index (BMI) and DM. A retrospective cohort study was performed with 10,087,903 participants of the Korean National Health Screening Program in 2009. The cohort was followed up to the date of TB incidence, death, or until December 31, 2018. We compared the incidence and risk of TB according to BMI category and DM. During the 7.3-year follow-up duration, the incidence of TB was 0.92 per 1000 person-years in normal weight participants without DM, 2.26 in normal weight participants with DM, 1.80 in underweight participants without DM, and 5.35 in underweight participants with DM. Compared to the normal weight participants without DM, the underweight participants without DM and the normal weight participants with DM showed a 2.21-fold (95% CI, 2.14–2.28) and a 1.51-fold (95% CI, 1.46–1.57) increased risk of TB, respectively. Furthermore, compared to the normal weight participants without DM, the underweight participants with DM showed a 3.2-fold increased risk of TB; however, the severely obese participants with DM showed a 0.4-fold decreased risk of TB. There was no significant joint effect of BMI and DM on the risk of incident TB in the overall population; a synergistic effect of underweight and DM was evident in participants < 65 years of age, current smokers, and heavy drinkers. In conclusion, being underweight or DM individually increases the risk of incident TB. Based on our study results, a focused screening of incident TB in patients with DM may be beneficial.